Anomalies of Midbrain/Hindbrain Development: Malformations of Cerebellum: Diagnosis, Classification, and Rehabilitative Hypothesis - Liotta, Emanuele; Dierna, Federica; Zanghì, Antonio; Salafia, Stefania; Vecchio, Michele; Chiaramonte, Rita; Cancemi, Giovanna; Belfiore, Giuseppe; Basile, Antonio; Ruggieri, Martino; Polizzi, Agata (Journal of Pediatric Neurology, 2024)
Extensive research has been conducted on the cerebellum, making it one of the most thoroughly investigated regions of the brain. It plays a fundamental role not only in motor control but also in motor learning and cognition. The development of the cerebellum is a lengthy process, beginning during the embryonic period up to the first years of life. This slow and protracted process makes it a vulnerable organ liable to different insults, responsible for many developmental disorders such as Dandy–Walker syndrome, medulloblastoma, dystroglicanopathy, pontocerebellar hypoplasia, thubulinopathies, and Jubert syndrome. Due to several factors, the true prevalence of cerebellar malformations is not known in most cases. The cerebellum undergoes development through following four fundamental stages:(1) Identification of the cerebellar region at the boundary between the midbrain and hindbrain.(2) Establishment of two cell proliferation compartments: firstly, Purkinje cells and deep cerebellar nuclei emerge from the ventricular zone of the metencephalic alar plate; secondly, granule cell precursors are generated from a separate proliferation compartment known as the upper rhombic lip.(3) Migration of granule cells toward the interior: granule precursor cells constitute the external granular layer (EGL), and during the initial postnatal year, granule cells migrate inward to their final position in the internal granular layer.(4) Formation of cerebellar circuitry and subsequent differentiation.Based on different types of involvement of the structures detected in the brain magnetic resonance, the classification of brainstem and cerebellar anomalies is divided into three categories: (1) mainly the cerebellum, (2) mainly the brain stem, and (3) both involved. This review will outline the developmental processes of the cerebellum and delve into common developmental disorders associated with it, including the Dandy–Walker syndrome, cerebellar hypoplasia, rhomboencephalosynapsis, lissencephaly, and gray matter heterotopias.
Keywords: cerebellar malformations; cerebellum; cerebellar region/hypoplasia/Dandy–Walker syndrome